Peningkatan Pengetahuan Masyarakat tentang Pemanfaatan Seledri (Apium graveolens L.) sebagai Antimikroba - Sari, Putri Eka; Suprapti, Tati; Elsha, Dwi (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
Infections caused by pathogenic microorganisms remain a major health challenge. One preventive promotive effort to reduce infection incidence is through the use of traditional medicinal plants, such as celery (Apium graveolens L.) which is known to have antimicrobial activity. This community service program aimed to increase the knowledge of PKK cadres in Klender Urban Village regarding the antimicrobial benefits of celery through educational outreach. The activity was held on June 12, 2025, involving 14 PKK cadres as participants. Evaluation was carried out using pre-test and post-test questionnaires, analyzed using the Wilcoxon test. The results showed a significance value of 0.002 (p<0.05), indicating a significant increase in knowledge after the intervention. The average percentage of correct answer increased by 37.2%. Additionally, all of participants demonstrated good knowledge levels in the post-test and none were in the poor category. These findings indicate that education through outreach is effective in improving community understanding of celery’s antimicrobial potential. Local plant-based education is expected to be a sustainable preventive strategy to improve public health.Keywords: education, celery, antimicrobial, knowledge PKK cadres